The emerging role of circadian rhythms in the development and function of thermogenic fat - Peng, Xuemin; Chen, Yong (Frontiers in Endocrinology, 2023)
Circadian rhythms regulate many biological processes in response to ambient influences. Disrupted circadian rhythm has been shown to be associated with obesity and obesity-related metabolic disorders. Thermogenic fat including brown and beige fat may play an important role in this process, since they display a high capacity to burn fat and release the stored energy as heat, contributing to the combat against obesity and its associated metabolic disorders. In this review, we summarize the relationship between the circadian clock and thermogenic fat and the prominent mechanisms which are involved in the regulation of the development and function of thermogenic fat by circadian rhythms, which may provide novel therapeutics for the prevention and treatment of metabolic diseases by targeting thermogenic fat in a circadian manner.